The complementary ingestion of the organizational support as a practice at the university pattern - Baadji, Hanan; Lounis, Faris (Technium Social Sciences Journal, 2022)
This theoretical study is under the title “The complementary ingestion of the organizational support as a practice at the university pattern”. It focuses on the aspects revealing the organizational support reality at the Algerian university pattern as a key point, showing all the mechanisms reflecting the organizational support concept, according to conceptual significances. It demonstrates its significance through the organizational support determinants, besides highlighting the concept within the theoretical approaches. It has been concluded with an overall research discussion about the organizational support continuity at the Algerian university according to the steps it went through.